Correlation between acupuncture dose and effectiveness in the treatment of knee osteoarthritis: a systematic review. Issue 5 (October 2019) - Sun, Ning; Tu, Jian Feng; Lin, Lu Lu; Li, Yong Ting; Yang, Jing Weng; Shi, Guang Xia; Lao, Li Xing; Liu, Cun Zhi
Background: Acupuncture is a widely used treatment for knee osteoarthritis, but evidence of its effectiveness from randomised controlled trials (RCTs) is contradictory. Objective: To systematically review RCTs to determine whether the effect of acupuncture is dose dependent for symptom management in knee osteoarthritis. Methods: Seven English/Chinese databases were searched through January 2017. Study quality was assessed using the Cochrane Collaboration tool. Slavin's qualitative best-evidence synthesis approach was used to provide methodological rigour. Included RCTs were separated into three categories according to the dose of acupuncture treatment: high dosage (HD), medium dosage (MD) and low dosage (LD). Correlation between dose and effect of treatment was analysed. Results: Eight RCTs with a total of 2106 subjects met the eligibility criteria. Numbers of studies using the various doses of acupuncture were 1 for LD, 1 for MD and 6 for HD, respectively. Compared with LD and MD acupuncture treatments, strong evidence showed that there was a positive correlation between HD acupuncture treatment and positive outcomes. Conclusion: The effect of acupuncture may be associated with dose of acupuncture, with a higher dosage related to better treatment outcomes in terms of relief of pain and dysfunction in patients with knee osteoarthritis.